Carmen : from silent film to MTV - Perriam, Christopher; Davies, Ann, 1961- (Critical studies (Amsterdam, Netherlands), 2005)
Since Prosper Mérimée and Georges Bizet (with his librettists Meilhac and Halévy) brought the figure of the Spanish Carmen to prominence in the nineteenth century an astonishing eighty or so film versions of the story have been made. This collection of essays gathers together a unique body of scholarly critique focused on that Carmen narrative in film. It covers the phenomenon from a number of aspects: cultural studies, gender studies, studies in race and representation, musicology, film history, and the history of performance. The essays take us from the days of silent film to twenty-first ce.